Synthesis and Characterization of Hollow and Non-Hollow Monodisperse Colloidal TiO2 Particles - Eiden-Assmann, Stefanie; Widoniak, Johanna; Maret, Georg (My University, 2005)
Monodisperse spherical hollow and non-hollow titania particles of variable sizes are produced in a sol–gel synthesis from Ti(EtO)4 in ethanol. Hollow spherical particles of rutile were obtained by coating colloidal polystyrene beads with a titanium oxide hydrate layer and subsequently calcination at elevated temperatures in oxygen atmosphere. The non-hollow titania particles were produced in the presence of salt or polymer solution. The influence of different salt ions or polymer molecules on the size and on the size distribution of the non-hollow particles was investigated. Nitrogen absorption measurements revealed that the addition of polymers yields porous titania colloids.
Keywords: Sol-gel synthesis; Titania particles; N-MAS-NMR; Powder x-ray diffraction; Porosity; 530